Inovasi Alat Pengemasan Tempe dalam Meningkatkan Produktivitas dengan Pendekatan Antropometri dan Penilaian Biaya - Prima, Sabrian; Murnawan, Hery (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Tempeh, a soybean-based product fermented by the fungus Rhizopus oligosporus, is a traditional Indonesian food known for its high nutritional value, particularly as a source of plant-based protein. The Tempeh Production House "Mas Alfin" employs both Make-To-Order (MTO) and Make-To-Stock (MTS) production systems to meet customer demands, including partnerships with catering companies. However, the tempeh production process at this facility faces efficiency challenges, particularly in the manual packaging stage, which is time-consuming and causes ergonomic complaints among workers. This study aims to develop a semi-automatic and ergonomic packaging tool to enhance production efficiency, reduce worker complaints, and improve product competitiveness. Based on anthropometric measurements, the packaging tool is designed with the following specifications: tool height of 150 cm, hand reach for input of 68.5 cm, and output height of 61.5 cm. The tool can reduce packaging time from 75 seconds to 36 seconds per kilogram, increase production capacity by up to 108%, and lower the production cost from IDR 7,058 to IDR 6,083 per 500 grams. The investment in this packaging tool achieves a payback period of 8 days, with a daily cost of IDR 383,400. Keywords: Anthropometry, Design, Tempeh